Glaucoma Clinical Research: Trends in Treatment Strategies and Drug Development - Storgaard, Line; Tran, Thuy Linh; Freiberg, Josefine Clement; Hauser, Alexander S.; Kolko, Miriam (Frontiers in Medicine, 2021)
Abstract Purpose: To investigate the trends and progresses in glaucoma research by searching two major clinical trial registries; clinicaltrials.gov and australianclinicaltrials.gov. Methods: All clinical trials with glaucoma covered by Clinicaltrials.gov and Australianclinicaltrials.gov starting the study before 1 January 2021 were included. Trials evaluating glaucoma treatment were separated from non-treatment trials and divided into three major categories: “laser treatment”, “surgical treatment” and “medical treatment”. In the category of “medical treatment”, new compounds and their individual targets were identified and subcategorized according to treatment strategy; intraocular pressure (IOP)-lowering, neuroprotective or vascular. The phase transition success rates were calculated. Results: 1537 trials were identified. 63 % (n=971) evaluated glaucoma treatment, of which medical treatment accounted for the largest proportion (53%). The majority of medical trials evaluated IOP-lowering compounds, while trials with neuroprotective or vascular compounds accounted for only 5 % and 3 %, respectively. 88 new compounds were identified. Phase I, II and III transition success rates were 63 %, 26 % and 47 %, respectively. Conclusion: The number of clinical trials in glaucoma research has increased significantly over the last 30 years. Among the most recently evaluated compounds, all three main treatment strategies were represented, but clinical trials in neuroprotection and vascular modalities are still sparse. In addition to traditional medicines, dietary supplements and growth factors are assessed for a potential anti-glaucomatous effect. Phase II and III success rates were below previously reported success rates for all diseases and ophthalmology in general. A stricter phenotyping of patients can improve the success rates in glaucoma and ophthalmological research and gain a better understanding of responders and non-responders.